Chapter 7. Computers in Formulation development and Screening Designs (Computer Aided Drug Development, 2024)
AuthorDr. Venkateswara Reddy Basu Professor and Head, Department of Pharmaceutics, Sri. K. V. College of Pharmacy, Chikkaballapura, Karnataka, IndiaAbstractComputer-aided formulation development and screening designs represent a paradigm shift in pharmaceutical research and development, offering sophisticated approaches to optimize product development processes. This modern methodology integrates advanced computational tools, statistical analysis, and experimental design principles to systematically evaluate and optimize pharmaceutical formulations. The implementation of screening designs within computational frameworks enables rapid evaluation of multiple formulation variables while minimizing resource utilization and experimental burden. These approaches facilitate the systematic exploration of formulation space, allowing researchers to make informed decisions based on statistical evidence rather than traditional trial-and-error methods. The integration of Quality by Design principles with computational tools ensures a thorough understanding of the relationship between formulation variables and product attributes. Modern computational platforms incorporate various statistical methods, optimization algorithms, and data analysis tools to predict formulation behavior and optimize product characteristics.Keywords: Computer-aided formulation; Screening designs; Experimental design; Formulation optimization; Statistical modelling; Quality by Design; Process optimizationView PDF